Mass mortality of the keratose sponge Sarcotragus foetidus in the Aegean Sea (Eastern Mediterranean) correlates with proliferation of Vibrio bacteria in the tissues - Dinçtürk, Ezgi; Öndes, Fikret; Leria, Laia; Maldonado, Manuel (Frontiers in Microbiology, 2023)
In the last two decades, episodes of mass mortality in benthic communities have often been associated with climatic anomalies, but the ultimate mechanisms through which they lead to death have rarely been identified. This study reports a mass mortality of wild sponges in the Aegean Sea (Turkey, Eastern Mediterranean), which affected the keratose demosponge Sarcotragus foetidus in September 2021. We examined the occurrence of thermo-dependent bacteria of the genus Vibrio in the sponges, identified through 16S rRNA of colonies isolated from sponge tissue in specific culturing media. Six Vibrio sequences were identified from the sponges, three of them being putatively pathogenic (V. fortis, V. owensii, V. gigantis). Importantly, those Vibrios were isolated from only tissues of diseased sponges. In contrast, healthy individuals sampled in both summer and winter led to no Vibrio growth in laboratory cultures. A 50-year record of sea surface temperature (SST) data for the study area reveals a progressive increase in temperature from1970 to 2021, with values above 24 ºC from May to September 2021, reaching an absolute historical maximum of 28.9 ºC in August 2021. We hypothesize that such elevated SST values maintained for several months in 2021 promoted proliferation of pathogenic Vibrio species (thermo-dependent bacteria) in S. foetidus, triggering or aggravating the course of sponge disease. Thus, vibrioisis emerges as one of the putative mechanisms through which global water warming in the Mediterranean Sea translates into sponge mortality. The historical time course of temperature data for the studied area in the Aegean Sea predicts that recurrent waves of elevated SST are likely to occur in the coming summers. If so, recurrent disease may eventually eliminate this abundant sponge from the sublittoral in the midterm, altering the original bathymetric distribution of the species and compromising its ecological role.